Validity of an Authentic Deed Signed Without Being Read and Outside Notary Office Hours - Darmawan, Yoga (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research is intended to find out and analyze the signing of authentic deeds which were done briefly with/or not reading the deed outside the Notary's office hours and also to find out and analyze the validity of deeds whose signing was done briefly with/or not reading the deed outside of hours notary office. This research uses a normative juridical approach, namely solving facts that constitute legal problems. Research that discusses problems is based on statutory regulations or literature related to these problems. The approach used in this research is a statutory approach and a conceptual approach. This research uses 2 (two) theories, namely the theory of authority and the theory of legal certainty. Problems occur when the Notary is negligent or underestimates the signing process which without realizing it can have legal impacts on the Notary and/or the parties binding themselves in the Deed. Notaries are given the authority by attribution to make authentic deeds and read the deed before it is signed by the presenters. The main purpose of reading the deed is to make corrections and clarifications to the deed made to provide legal certainty to the parties.Keywords: Deed; Notary; Signing; Working.